Sex-differences in outcomes after PCI or CABG for left main disease: from the DELTA registries. (25th November 2020) - Moroni, F; Beneduce, A; Giustino, G; Breite, I; Park, S.J; Daemen, J; Morice, M.C; Nakamura, S; Meliga, E; Cerrato, E; Makkar, R; Valgimigli, M; et al.
Abstract: Background: Women have worse outcomes than men after PCI, with some studies suggesting a lower mortality of CABG vs PCI in females. Purpose: To assess the outcomes of CABG and PCI according to sex in a large registry population of patients with unprotected left main coronary artery (ULMCA) disease. Methods: The DELTA and DELTA 2 registries are two multicentric, prospective registries evaluating the outcomes of subjects undergoing coronary revascularization for ULMCA disease. Results: Total population was 6253 patients, 27% women. Table 1 shows baseline clinical characteristics. Median follow up was of 880 days. Women undergoing CABG had lower incidence of death, myocardial infarction (MI) or cerebrovascular accidentc (CVA) (HR 0.53, 95% CI 0.35–0.79) and a lower risk of death (HR 0.40, 95% CI 0.24–0.67). No significant differences were observed in men (Figure 1A). SIgnificant interaction was observed between sex and revascularization strategy for both outcomes (p<0.01-Figure 1B). CABG was associated with lower risk of target-vessel and target-lesion revascularization consistently inwomen and men (pint=0.49 and pint=0.89, respectively–Figure 1B). Conclusions: In women undergoing coronary revascularization for ULMCA disease, CABG is associated to lower risk of death, MI or CVA. Further dedicated studies are needed to determine the optimal revascularization strategy in women with ULMCA disease. Funding Acknowledgement: Type of funding source: None